Highly Siderophile Element and Os Isotope Systematics of Volcanic Rocks at Divergent and Convergent Plate Boundaries and in Intraplate Settings - Gannoun A.; Burton K.W.; Day J.M.D.; Harvey J.; Schiano P.; Parkinson I. (My University, 2016)
Terrestrial magmatism is dominated by basaltic compositions. This definition encompasses mid-ocean ridge basalts (MORB), which account for more than eighty percent of Earth’s volcanic products and which are formed at divergent oceanic plate margins, as well as intraplate volcanic rocks such as ocean island basalts (OIB), continental flood basalts (CFB) and continental rift-related basalts, and highly magnesian ultramafic volcanic rocks that dominantly occur in Archean terranes, termed komatiites. All of these broadly basaltic rocks are considered to form by partial melting of the upper mantle, followed by extraction from their source regions and emplacement at the Earth’s surface.
Keywords: siderophile element; Os isotope; volcanic rocks